1987
DOI: 10.1159/000153700
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Hp 1 and Sickle Cell Disease

Abstract: The distribution of gene frequencies and types for haptoglobin (Hp) were studied in a normal black population and one with sickle cell disease. The statistical analysis of our findings indicated a significant association between sickle cell disease and the Hp 1 type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 12 publications
5
7
2
Order By: Relevance
“…We determined the Hp phenotype in sickle cell diseases patients. The haptoglobin phenotype Hp1-1 frequency was high (77.3%) among sickle cell anaemia , and this agreed with the result of Ostrowski et al,1987, who found association of Hp1 and sickle cell disease. Patients with sickle cell anaemia usually die from malaria in tropical Africa, (Adeloye et al, 1971;Konotey et al,1971 ;Onwubalili, 1983).…”
Section: Resultssupporting
confidence: 86%
“…We determined the Hp phenotype in sickle cell diseases patients. The haptoglobin phenotype Hp1-1 frequency was high (77.3%) among sickle cell anaemia , and this agreed with the result of Ostrowski et al,1987, who found association of Hp1 and sickle cell disease. Patients with sickle cell anaemia usually die from malaria in tropical Africa, (Adeloye et al, 1971;Konotey et al,1971 ;Onwubalili, 1983).…”
Section: Resultssupporting
confidence: 86%
“…Because of this polymorphism, the Hp gene is a prime candidate of investigation for any modulatory association with SCD pathophysiology or its subphenotypes. The only previous pertinent studies have been among American and Brazilian patients, for both of whom an association with the Hp 1-1 phenotype was reported [19,20] . The current study is the first among Arab and African SCD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hp 1-1 protects against atherosclerosis and other vascular complications of diabetes mellitus and is also protective in retinal hemorrhage [17,18] . There are two previous studies of Hp phenotypes in SCD, one from the USA [19] and the other from Brazil [20] , both of which reported a strong association with Hp 1-1 phenotype. Although there was no mention of the ␤ S -globin gene haplotypes in the patients, it is known that SCD in both populations is associated with haplotypes characterized by low Hb F. Moreover, the two groups of patients share similar ancestral histories, being descendants of Africans brought to the Americas as slaves.…”
Section: Introductionmentioning
confidence: 99%
“…However, the physiological importance of these interactions and their implications in normal physiology and diseases are still not well understood. Nevertheless, the strong conservation of Hp gene and protein, and the association of different Hp phenotypes and hemolytic diseases such as sickle cell anemia 106 and malaria, [107][108][109][110][111] strongly suggest that Hp and hemoglobin interactions are physiologically important.…”
Section: Discussionmentioning
confidence: 99%